Social participation and language use of the people with aphasia through the eyes of their carers - Maviş, İlknur; Topbaş, Saime Seyhun; Özmen, Anıl (Sage Publications Ltd, 2016)
[Abstract Not Available]
WOS: 000386912100615
Keywords: Neurosciences; Neurology; Cardiovascular System; Cardiology